SISTEM KEAMANAN HELM BERBASIS IOT DENGAN LAYANAN AKSES LOKASI MENGGUNAKAN TELEGRAM - Wandari, Fitri; Meisya Suandari; Irwan; Ocsirendi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
Helmet theft is a common problem for motorcycle users, especially on campuses. An Internet of Things (IoT) security system with location access via Telegram is designed to enhance helmet security. This system uses the HC-05 Bluetooth module as a master on the motorcycle and a slave on the helmet. If the connection is lost, a buzzer will sound and the ESP8266 module will send a notification to Telegram. The SIM900A module receives user commands, allowing them to send a "FIND" message to determine the location of the helmet or motorcycle based on data from the GPS module. This system enables real-time monitoring and tracking of lost helmets via Telegram.